Method for preparing hard carbon material through hot-pressing carbonization and application
The hard carbon material prepared by the hot pressing carbonization method solves the problem of low efficiency of the first circle of the negative electrode material of sodium ion battery, achieves high platform capacity and high first circle of the Coulomb efficiency, and improves the cycle life and energy density of the battery.
Patent Information
- Application Number
- CN202510198465.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-22
- Publication Date
- 2025-04-29
AI Technical Summary
The negative electrode material of existing sodium ion batteries is inefficient in the first cycle, which leads to the inability to effectively utilize part of the battery during the first charge and discharge, affecting the cycle life and energy density of the battery.
Hard carbon materials are prepared by hot-pressed carbonization method. By using hazelnut shells as raw materials, high-speed crushing, ball milling and hot-pressed carbonization, carbon materials with high platform capacity and high first-circle Coulomb efficiency are prepared.
The prepared hard carbon material has a long platform capacity in the low voltage zone, the first circle of Coulomb efficiency reaches 91.25%, and the charging specific capacity can reach 314.6 mAh/g at a current density of 30 mA/g, which significantly improves the electrochemical performance of sodium ion batteries.
Smart Images

Figure CN119898757A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical energy storage and relates to a method for preparing hard carbon material by hot pressing carbonization and application thereof. Background Art
[0002] As a "substitute" technology for lithium batteries, sodium-ion batteries use cost advantages as their selling point, and have unique advantages in charge and discharge rates, high and low temperature performance, and safety. With the large-scale production of related products, the application prospects of sodium batteries continue to be expected. As an important component of sodium-ion batteries, the selection and microstructure of negative electrode materials play a decisive role in the electrochemical performance of sodium-ion batteries.
[0003] Compared with negative electrode materials based on alloy reactions (such as tin, antimony and bismuth) and conversion reactions (such as oxides of transition metals such as iron, cobalt, nickel and manganese), carbon materials are regarded as the most promising negative electrode materials for application due to their advantages such as low cost, stable physicochemical properties and easily adjustable structure. Among them, the application of hard carbon in sodium storage has attracted much attention. Structurally, hard carbon has randomly oriented, highly disordered graphene nanosheets and nanographite crystallites, as well as abundant defects. These structures are sites for sodium ion adsorption and intercalation, showing slope region capacity in the electrochemical curve. In addition, the interior of hard carbon has pores of different sizes, which provide more active sites for sodium ion storage at low potential (~0.1 V).
[0004] However, the half-cell composed of hard carbon and sodium metal is difficult to be used as a device for practical application, and is usually matched with the positive electrode to form a full cell. Considering the performance of the full cell, the lower the electrode potential of the negative electrode, the more conducive it is to the improvement of the energy of the full cell. Therefore, current research has focused on the preparation of hard carbon with high platform capacity. In addition, the low first-cycle coulomb efficiency of the negative electrode means that part of the battery capacity cannot be effectively utilized in the first cycle, which may be due to factors such as irreversible reactions of electrode materials, decomposition of electrolytes, and formation of solid electrolyte interface films. These irreversible reactions and processes will lead to the loss of electrode materials and capacity decay, while making it difficult to exert the capacity of the positive electrode, thereby reducing the cycle life and energy density of the battery. Therefore, the preparation of hard carbon materials with high platform capacity and first-cycle coulomb efficiency is extremely important for the development of sodium-ion batteries. At present, the preparation of such high-quality hard carbon mainly includes more complex strategies such as chemical vapor deposition and high-temperature secondary carbonization. Summary of the invention
[0005] The purpose of the present invention is to provide a method and application of preparing hard carbon materials by hot pressing carbonization. The carbon material prepared by the method can be used as the negative electrode of a sodium ion battery. The method is simple and easy to operate. The raw materials used are easily available biomass raw materials. The obtained carbon material has the advantages of high capacity, high first-cycle coulombic efficiency and excellent rate performance.
[0006] The present invention is achieved through the following technical solutions.
[0007] The method for preparing hard carbon material by hot pressing carbonization described in the present invention comprises the following steps.
[0008] (S1) The hard carbon precursor was crushed by a high-speed pulverizer and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0009] Preferably, the hard carbon precursor is one or more of hazelnut shells, melon seed shells, and walnut shells.
[0010] (S2) A proper amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace. Under argon conditions, hot-pressing carbonization is performed at 600-1500 °C for 10-60 min at a heating rate of 10-50 °C / min. During the carbonization process, a pressure of 1-30 MPa is applied to the precursor. After the reaction is completed, the precursor is cooled to room temperature to obtain hard carbon powder.
[0011] Preferably, the carbonization conditions are a temperature of 1200-1400° C., a carbonization time of 10 min, a heating rate of 30° C. / min, and a pressure of 1.5-3 Mpa.
[0012] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, and then washing with water, the hard carbon powder is dried in a vacuum oven at 60° C. to obtain a hard carbon active material.
[0013] Furthermore, in step (S3), the water is distilled water or deionized water, and the final effect of water washing is that the supernatant of the solution is neutral.
[0014] The present invention discloses a method for preparing a hard carbon material by hot pressing carbonization as a negative electrode for a sodium ion battery. The negative electrode sheet of the sodium ion battery is prepared by coating a mixed slurry of active material, carbon black and a binder on a carbon-coated aluminum foil, wherein the weight proportion of the binder is 10%, and the weight ratio of the active material to the carbon black is 3.5:1-18:1.
[0015] The binder is preferably sodium carboxymethyl cellulose (CMC).
[0016] Compared with the existing methods, the present invention has the following technical advantages.
[0017] Provided is a method and application for preparing hard carbon materials by hot pressing carbonization. The present invention uses inexpensive hazelnut shells as raw materials, and through a one-step rapid hot pressing carbonization method, accurately controls the graphite-like micro-region structure and pore structure of the material, transforms the hazelnut shells into a carbon material with a long platform capacity in the low voltage region, and at the same time greatly reduces the specific surface area of the material, and improves its first-cycle coulomb efficiency when used as the negative electrode of a sodium ion battery. The material is used as the negative electrode of a sodium ion battery, and its charging specific capacity can reach 314.6 mAh / g at a current density of 30 mA / g, wherein the platform capacity is 210.7 mAh / g, and the first-cycle coulomb efficiency is 91.25%. The present invention provides a method for preparing a carbon material with low preparation cost, simple process, and excellent performance, and uses it as a negative electrode material in a sodium ion secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the X-ray diffraction pattern of the hazelnut shell-derived hard carbon negative electrode material prepared by hot pressing in Example 1.
[0019] Figure 2 This is a scanning electron microscope image of the hazelnut shell-derived hard carbon negative electrode material prepared by hot pressing in Example 1.
[0020] Figure 3 This is the small-angle X-ray scattering pattern of the hazelnut shell-derived hard carbon negative electrode material prepared by hot pressing in Example 1.
[0021] Figure 4 This is a nitrogen adsorption-desorption curve of the hazelnut shell-derived hard carbon negative electrode material prepared by hot pressing in Example 1.
[0022] Figure 5 This is the charge and discharge curve of the hazelnut shell derived hard carbon negative electrode material prepared by hot pressing in Example 1.
[0023] Figure 6 This is the rate performance diagram of the hazelnut shell derived hard carbon negative electrode material prepared by hot pressing in Example 1.
[0024] Figure 7 This is the charge and discharge curve of the hard carbon negative electrode material prepared by hot pressing in Example 2.
[0025] Figure 8 This is the charge and discharge curve of the hard carbon negative electrode material prepared by hot pressing in Example 3.
[0026] Fig. 9 This is the charge and discharge curve of the hard carbon negative electrode material prepared by hot pressing in Example 4.
[0027] Fig.10 This is the charge and discharge curve of the hard carbon negative electrode material prepared by hot pressing in Example 5.
[0028] Fig.11This is the charge and discharge curve of the hard carbon negative electrode material prepared by hot pressing in Example 6.
[0029] Fig.12 This is the charge and discharge curve of the hard carbon negative electrode material prepared by hot pressing in Example 10.
[0030] Fig.13 This is the charge and discharge curve of the hard carbon negative electrode material prepared by hot pressing in Example 11. DETAILED DESCRIPTION
[0031] In order to make the advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical means involved in each embodiment described in the examples can be diversified and are not limited to the experimental technical means. Example 1
[0032] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0033] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0034] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0035] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 8:1.
[0036] Figure 1 This is the X-ray diffraction pattern of the hard carbon negative electrode material of this embodiment. From the diffraction pattern, it can be found that the sample is a typical amorphous carbon structure. The diffraction angle of its amorphous peak is 24.17°, corresponding to a carbon interlayer spacing of 3.679 nm. A wider interlayer spacing is conducive to the intercalation of sodium ions.
[0037] Figure 2 This is a scanning electron microscope image of the hard carbon negative electrode material of this embodiment. The morphology of the hard carbon is an irregular block structure.
[0038] Figure 3 This is a small-angle X-ray scattering diagram of the hard carbon negative electrode material of this embodiment. The scattering peak around 0.1 1 / nm proves the existence of micropores. The micropores provide space for the filling of sodium ions.
[0039] Figure 4 The nitrogen adsorption and desorption curve of the hard carbon negative electrode material of this embodiment is shown in Figure 2. The sample exhibits typical adsorption characteristics of mesoporous structure. The BET specific surface area is 2.9646 m 2 / g. The very small specific surface area can reduce the consumption of electrolyte and help improve the first-cycle coulombic efficiency of the material.
[0040] Figure 5 The first three cycles of charge and discharge curves of the hard carbon negative electrode material of this embodiment are shown in Figure 1. The first cycle charge capacity is 314.6 mAh / g, the discharge capacity is 344.8 mAh / g, and the coulombic efficiency is 91.25%. The coulombic efficiency of the second and third cycles is stable at ~100%.
[0041] Figure 6 This is the rate performance diagram of the modified YP-50F capacitor activated carbon negative electrode material of this embodiment. When the current density reaches 500 mA / g, the capacity of the sample is 254.7 mAh / g. Example 2
[0042] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0043] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 600 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0044] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0045] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 8:1.
[0046] Figure 7The first three cycles of charge and discharge curves of the hard carbon negative electrode material of this embodiment are shown in Figure 1. The first cycle charge capacity is 186.3 mAh / g, the discharge capacity is 248.8 mAh / g, and the coulombic efficiency is 74.86%. The coulombic efficiency of the second and third cycles is stable at ~100%. Example 3
[0047] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0048] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 800 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0049] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0050] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 8:1.
[0051] Figure 8 The first three cycles of charge and discharge curves of the hard carbon negative electrode material of this embodiment are shown in Figure 1. The first cycle charge capacity is 202.3 mAh / g, the discharge capacity is 269.9 mAh / g, and the coulombic efficiency is 74.89%. The coulombic efficiency of the second and third cycles is stable at ~100%. Example 4
[0052] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0053] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1000 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0054] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0055] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 6:1.
[0056] Fig. 9 The first three cycles of charge and discharge curves of the hard carbon negative electrode material of this embodiment are shown in Figure 1. The first cycle charge capacity is 250.3 mAh / g, the discharge capacity is 306.2 mAh / g, and the coulombic efficiency is 81.75%. The coulombic efficiency of the second and third cycles is stable at ~100%. Example 5
[0057] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0058] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1200 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0059] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0060] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 8:1.
[0061] Fig.10 The first three cycles of charge and discharge curves of the hard carbon negative electrode material of this embodiment are shown in Figure 1. The first cycle charge capacity is 274.8 mAh / g, the discharge capacity is 320.0 mAh / g, and the coulombic efficiency is 85.87%. The coulombic efficiency of the second and third cycles is stable at ~100%. Example 6
[0062] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0063] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1400 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0064] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0065] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 10:1.
[0066] Fig.11 The first three cycles of charge and discharge curves of the hard carbon negative electrode material of this embodiment are shown in Figure 1. The first cycle charge capacity is 295.1 mAh / g, the discharge capacity is 323.0 mAh / g, and the coulombic efficiency is 91.36%. The coulombic efficiency of the second and third cycles is stable at ~100%. Example 7
[0067] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0068] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1500 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0069] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0070] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 13:1. Example 8
[0071] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0072] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 10 min under argon conditions with a heating rate of 10 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0073] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0074] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 18:1. Example 9
[0075] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0076] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 10 min under argon conditions with a heating rate of 50 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0077] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0078] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 5:1.
[0079] Example 10.
[0080] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0081] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 9 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0082] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0083] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 8:1.
[0084] Fig.12 The first three cycles of charge and discharge curves of the hard carbon negative electrode material of this embodiment are shown in Figure 1. The first cycle charge capacity is 265.9 mAh / g, the discharge capacity is 309.7 mAh / g, and the coulombic efficiency is 85.87%. The coulombic efficiency of the second and third cycles is stable at ~100%.
[0085] Example 11.
[0086] (S1) After the hazelnut shells were crushed by a high-speed crusher, they were ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0087] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 15 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0088] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0089] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 8:1.
[0090] Fig.13 The first three cycles of charge and discharge curves of the hard carbon negative electrode material of this embodiment are shown in Figure 1. The first cycle charge capacity is 250.2 mAh / g, the discharge capacity is 311.1 mAh / g, and the coulombic efficiency is 80.42%. The coulombic efficiency of the second and third cycles is stable at ~100%.
[0091] Example 12.
[0092] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0093] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 5 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0094] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0095] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 15:1.
[0096] Example 13.
[0097] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0098] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 30 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0099] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0100] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 8:1.
[0101] Example 14.
[0102] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0103] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 40 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0104] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0105] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 3.5:1.
[0106] Example 15.
[0107] (S1) The hazelnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0108] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 60 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0109] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0110] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 8:1.
[0111] Example 16.
[0112] (S1) After the melon seed shells were crushed by a high-speed crusher, they were ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0113] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0114] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0115] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 8:1.
[0116] Example 17.
[0117] (S1) The walnut shells were crushed by a high-speed crusher and then ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30.
[0118] (S2) An appropriate amount of precursor powder is loaded into a hot-pressed carbonized graphite mold with an inner diameter of 2 cm. The mold is placed in an induction hot-pressing furnace and hot-pressed and carbonized at 1300 °C for 10 min under argon conditions with a heating rate of 30 °C / min. During the carbonization process, a pressure of 3 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder.
[0119] (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, washing with deionized water until the washing liquid is neutral, drying in a vacuum oven at 60°C for later use.
[0120] (S4) The carbonized carbon material is uniformly mixed with carbon black and a binder to prepare a slurry, which is then coated on a carbon-coated aluminum foil to obtain a carbon electrode. The weight ratio of the binder is 10%, and the weight ratio of the active material to the carbon black is 8:1.
[0121] The carbon pole piece prepared in the above embodiment was used as the negative electrode of the sodium ion battery, and the battery was assembled in a glove box filled with argon, wherein the carbon pole piece, glass fiber and sodium sheet were used as the working electrode, diaphragm and counter electrode, respectively. A traditional electrolyte (150 μL) was added to each battery. The traditional electrolyte is ethylene glycol dimethyl ether as a solvent and sodium hexafluorophosphate as a solute. After the assembly was completed and rested at 25°C for 4 hours, the charge and discharge cycle was performed between 0.001-2.5 V at a current density of 30 mA / g to perform relevant tests on sodium ion batteries.
[0122] The method of the present invention is easy and controllable, and a carbon material with high capacity, high stability and high rate performance is prepared by a one-step hot pressing carbonization method, which provides certain guiding significance for further promoting the development of sodium ion batteries.
[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, improvement and replacement made within the design concept and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a hard carbon material by hot pressing carbonization, characterized in that The steps include: (S1) After the hard carbon precursor is crushed by a high-speed pulverizer, it is ball-milled in a planetary ball mill at a speed of 500 r / min for 6 h with a mass ratio of material to agate beads of 1:30; (S2) filling an appropriate amount of precursor powder into a hot-pressed carbonized graphite mold, the inner diameter of the graphite mold is 2 cm, placing the mold in an induction hot-pressing furnace, and hot-pressing carbonizing at 600-1500 °C for 10-60 min under argon conditions, with a heating rate of 10-50 °C / min. During the carbonization process, a pressure of 1-30 MPa is applied to the precursor. After the reaction is completed, it is cooled to room temperature to obtain hard carbon powder; (S3) After washing the hard carbon powder obtained in step (S2) with dilute hydrochloric acid and dilute sodium hydroxide solution, and then washing with water, the hard carbon powder is dried in a vacuum oven at 60° C. to obtain a hard carbon active material.
2. The method for preparing hard carbon material by hot pressing carbonization according to claim 1, characterized in that The hard carbon precursor in step (1) is one or more of hazelnut shell, melon seed shell, and walnut shell.
3. The method for preparing hard carbon material by hot pressing carbonization according to claim 1, characterized in that The carbonization conditions of step (2) are as follows: temperature of 1200-1400°C, carbonization time of 10 min, heating rate of 30°C / min, and pressure of 1.5-3MPa.
4. The method for preparing hard carbon material by hot pressing carbonization according to claim 1, characterized in that The water in step (S3) is distilled water or deionized water, and the final effect of water washing is that the supernatant of the solution is neutral.
5. Use of the hard carbon material prepared by the method for preparing hard carbon material by hot pressing carbonization as described in claims 1-4 as a negative electrode of a sodium ion battery.
6. The use according to claim 5, characterized in that The negative electrode sheet of the sodium ion battery is prepared by coating a mixed slurry of active material, carbon black and binder on a carbon-coated aluminum foil. The weight proportion of the binder is 10%, and the weight ratio of the active material and carbon black is 3.5:1-18:1.
Citation Information
Cited By
Porous carbon material, preparation method thereof and application of porous carbon material in silicon-carbon negative electrode material
CN121528853A
Carbon-metal composite material based on in-situ confinement hot pressing as well as preparation method and application of carbon-metal composite material
CN122177851A